Image Processing and Numerical Methods in QR (Quick Response) Code efficient Decoding Using direct linear transformation method - Dr N.Gajalakshmi (Utilitas Mathematica, 2025)
The importance of numerical methods for image processing for reliable and efficient rapid response (QR) code decoding is investigated in this work. From image capture to data extraction, the process uses a number of cutting-edge methods to tackle real-world issues including noise, distortion, and changing illumination. The main stages of image processing are described, including perspective correction methods like homography estimation to precisely divide code blocks, feature detection algorithms to find the QR code inside the image, and preprocessing to improve contrast and lower noise. It also covers numerical techniques, such as statistical threshold algorithms, matrices for geometric transformations, and interpolation methods for image alignment and resizing. The study emphasizes how computational and numerical techniques work together to guarantee that QR codes